2007
DOI: 10.1016/j.jacc.2007.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Role of Right Ventricular Wall Motion Abnormalities in Risk Stratification and Prognosis of Patients Referred for Stress Echocardiography

Abstract: In patients referred for SE, RV wall motion analysis provides prognostic value independent of LV ischemia and ejection fraction and provides incremental value over rest and conventional SE variables. Right ventricular wall motion analysis should be routinely performed in patients referred for SE for effective risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 22 publications
(22 reference statements)
0
31
0
1
Order By: Relevance
“…97,131 Markers of high IHD event rates include not only the inability to perform an ETT but also numerous echocardiographic markers (Table 5). Among these are the number of abnormal segments at rest, the number of segments that become ischemic, the stress wall-motion score index, the change in wall-motion score index from rest to stress, an increase in systolic size with stress, LV ischemia that extends into the right ventricle, 132 an increase in end-systolic size, and a decrease in LV ejection fraction (LVEF) with stress. 109 Both short-and long-term follow-up studies show that stress echocardiography is predictive of subsequent MI, need for coronary revascularization, IHD death, and all-cause mortality.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…97,131 Markers of high IHD event rates include not only the inability to perform an ETT but also numerous echocardiographic markers (Table 5). Among these are the number of abnormal segments at rest, the number of segments that become ischemic, the stress wall-motion score index, the change in wall-motion score index from rest to stress, an increase in systolic size with stress, LV ischemia that extends into the right ventricle, 132 an increase in end-systolic size, and a decrease in LV ejection fraction (LVEF) with stress. 109 Both short-and long-term follow-up studies show that stress echocardiography is predictive of subsequent MI, need for coronary revascularization, IHD death, and all-cause mortality.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…It has been demonstrated that RV free wall dysfunction or lack of increase in tricuspid annular plane excursion during dobutamine stress are indicators of right coronary or multi-vessel disease 49,50 and predictive of prognosis. 51 …”
Section: Discussionmentioning
confidence: 99%
“…Patients with increased age, diabetes mellitus, hypertension, and known coronary artery disease were at higher risk of developing RV wall motion abnormalities. 2 Evaluating the RV can be difficult, as in our case, given the technically difficult images and use of perflutren contrast.…”
mentioning
confidence: 85%
“…3 When exercise-induced RV dilatation and hypokinesis may be seen on exercise stress echocardiography, its presence in the absence of LV abnormalities is unusual, 2 and, physicians should have a high suspicion for an abnormality of the pulmonary vasculature, specifically increased pulmonary vascular resistance. These manifestations become more evident when the cardiac output increases during stress and the RV lacks contractile reserve in the setting of increased pulmonary vascular resistance.…”
mentioning
confidence: 99%